Salt Used for the National School Nutrition Program (NSNP) in Rural Schools of Limpopo Province, South Africa, has Adequate Levels of Iodine - Ramugondo, Mpho; Mushaphi, Lindelani Fhumudzani; Mabapa, Ngoako Solomon (Biochemistry Research International, 2021)
Background. Salt iodisation is considered the most effective long-term public health intervention for achieving optimal iodine nutrition. Effective salt iodisation is a prerequisite for the sustainable elimination of iodine deficiency disorders. The aim of this study was to determine iodine concentration of salt used for the National School Nutrition Program (NSNP). Methods. A cross-sectional study was conducted in 359 food handlers from Vhembe and Mopani districts of Limpopo Province, South Africa. The questionnaire was administered to solicit data on demographic information, general questions on salt fortification, and iodine nutrition knowledge. After the interviews, two tablespoons of salt used for the NSNP food preparation was collected from 318 schools in small zip-lock plastic bags. The salt samples were coded and stored at room temperature and protected from light and moisture until the time of analysis. Salt iodine concentrations were determined at the North-West University (NWU) in Potchefstroom by means of the iCheck test method. Results. The median iodine concentration of both Mopani (31.65 ppm) and Vhembe (32.56 ppm) districts signified adequate iodine levels. Of 318 salt samples, 113 (71%) samples in Mopani and 104 (65%) in Vhembe had an iodine concentration of 15–64 ppm. A few (6%) food handlers in Mopani and almost half (45.9%) in Vhembe could correctly identify iodated salt as the main source of iodine. Almost half of the food handlers (%) in Mopani and 36.5% in Vhembe did not know which part of body needs iodine for functioning. Conclusion. More than 20 years after the implementation of the USI program, the result of the study shows that the international goal of 90% coverage is still far from being realised.